Cases in strategic management - Strickland, Alonzo J.; Thompson, Arthur A. (Boston, Mass. : Irwin/McGraw-Hill, 1998)
The manager as chief strategy maker and strategy implementer. Crafting strategy in single business companies. Crafting strategy in diversified companies. Implementing and executing strategy. Strategy, ethics, and social responsibility.
Keywords: Business; Management; Strategic planning; Strategic planning -- United States -- Case studies; Industrial management -- United States -- Case studies